The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1007/bf00315856
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-binding proteins 33 kDa, 35 kDa, and 65/67 kDa in normal rat and morris hepatoma tissues

Abstract: Polyclonal antibodies were raised against membrane-associated calcium-binding proteins (apparent molecular masses 65000 and 67000 (CBP 65/67) and 33000 and 35000 (CBP 33 and CBP 35)), which were isolated from rat liver and Morris hepatoma. Using immunoblotting, various amounts of CBP 33 and CBP 35 as well as CBP 65/67 were detected in most rat organs. Using alkaline phosphatase and monoclonal-anti-alkaline phosphatase antibodies (APAAP), all the calcium-binding proteins were detected by immunohistochemical tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The cruvirus-binding protein we found probably corresponds to ancial question is whether binding of influenza virus to annexin nexin V. Further experiments showed that infection of influ-V (or annexin 33 kDa) is an essential step for infection. Anenza viruses could be inhibited by externally added phosphonexins are thought to be both intracellular and plasma memlipids as well as by antiserum against annexin V. These results brane components [10][11][12]. If the binding of viral phospholisubstantiated our view that annexins may serve as a second pids to the annexins of the plasma membrane is an essential receptor for these viruses, step for infection, externally added phospholipids should compete in this reaction, resulting in the inhibition of virus infec-2.…”
mentioning
confidence: 89%
“…The cruvirus-binding protein we found probably corresponds to ancial question is whether binding of influenza virus to annexin nexin V. Further experiments showed that infection of influ-V (or annexin 33 kDa) is an essential step for infection. Anenza viruses could be inhibited by externally added phosphonexins are thought to be both intracellular and plasma memlipids as well as by antiserum against annexin V. These results brane components [10][11][12]. If the binding of viral phospholisubstantiated our view that annexins may serve as a second pids to the annexins of the plasma membrane is an essential receptor for these viruses, step for infection, externally added phospholipids should compete in this reaction, resulting in the inhibition of virus infec-2.…”
mentioning
confidence: 89%
“…Recently a group of calcium binding proteins (CBP) from rat liver was isolated and characterized in our laboratory (JosiC et al, 1990). The biochemical and immunological analysis indicated that these CBPs meet all the valid criteria for annexins.…”
Section: Discussionmentioning
confidence: 99%
“…CBP 65/67 was isolated from liver plasma membranes by stepwise extraction and subsequent HPLC as reported previously (JosiC et al, 1985(JosiC et al, , 1990. After preparative electrophoresis on a 10% SDS gel, the CBP65 and the CBP67 polypeptides were separated after detection by Scheele staining (Scheele et al, 1981).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations